(untitled) (Baghdad Science Journal, 2025)
The building of Basrah University located in a rural area at Gramat Ali, its consist of seven colleges and very high number of students, lecturers ,and employers. Therefore, the intersections which leading to university building suffer congestion at morning peak hour (8-9) A.M and evening peak hour (2-3) P.M. In this study we collected the data in intersections which leading to university building at peak hour at same time, then we had analysis this data by using the highway capacity manual (HCM) and program (HCS). Also, we collected that data in University entries with classification of vehicles according to types and number of passengers at peak hour. Then we studied the number of proposals to riddance the congestion, such as the effect of vehicles prohibition which one and two passenger to entry in University at peak hour. This proposal will riddance of the congestion at University entries and intersections.